Consumer behaviour and supermarkets in Argentina - Rodríguez, Elsa Mirta M. (2002)
This article examines supermarket development from the perspective of differences over regions and categories of consumers. It shows that, controlling for region, the more the education, income, durable assets (car, refrigerator) and consumer credit (credit card) of the consumer, the greater the probability that he/she will shop at a supermarket. Controlling for personal characteristics, living in a northern region (poorer, more rural, poorer infrastructure) reduces the probability of shopping at a supermarket. Finally, Argentinian consumers are less likely to buy fresh fruit and vegetables, red meat, and bread at a supermarket, as they would rather buy these from shops offering personal attention and service for those products.